2018
DOI: 10.1097/md.0000000000013512
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of atopic dermatitis with stroke and myocardial infarction

Abstract: Background:Lots of previous reports have suggested a potential association of atopic dermatitis (AD) with stroke and myocardial infarction (MI). However, the result is still controversial, Consequently, we conducted this meta-analysis to estimate the relationship of AD with Stroke and MI.Methods:PubMed, Embase, and Web of Science databases were searched from inception to June 2018. Stroke and MI were considered as a composite endpoint. We calculated pooled hazard ratios (HRs) with 95% confidence intervals (CIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
(85 reference statements)
5
15
0
Order By: Relevance
“…A possible explanation could be cellular pathways such as mast cell release linking allergy in asthma with coronary heart disease 36. The hypothesis of inflammatory pathways as a possible common mechanism is compatible with at recent finding of an increased risk only present in individuals with active asthma37 and also in line with observed associations between atopic dermatitis and myocardial infarction 38. Furthermore, the observed association between presence of allergy in asthma and coronary heart disease could be dependent on the late-phase reaction and chronic allergic inflammation involving mediators such as transforming growth factor α,39 a cytokine that has been associated with coronary heart disease 40.…”
Section: Discussionsupporting
confidence: 76%
“…A possible explanation could be cellular pathways such as mast cell release linking allergy in asthma with coronary heart disease 36. The hypothesis of inflammatory pathways as a possible common mechanism is compatible with at recent finding of an increased risk only present in individuals with active asthma37 and also in line with observed associations between atopic dermatitis and myocardial infarction 38. Furthermore, the observed association between presence of allergy in asthma and coronary heart disease could be dependent on the late-phase reaction and chronic allergic inflammation involving mediators such as transforming growth factor α,39 a cytokine that has been associated with coronary heart disease 40.…”
Section: Discussionsupporting
confidence: 76%
“…The underlying mechanism for this small association remains unclear. As previous studies have reported that people with severe atopic eczema are already at higher risk of cardiovascular disease, 5,6 our findings are largely reassuring for patients and practitioners.…”
Section: Discussionsupporting
confidence: 80%
“…Ye et al provided similar evidence in humans [ 40 ]. In the last 5 years, studies of psoriasis [ 6 ] and dermatitis [ 7 ] have similarly determined that skin inflammation likely increases the risk of cardiovascular disease. Therefore, the development of a skin-specific DNAm age predictor can offer a powerful tool for the comprehension of skin diseases and how it may influence overall organismal health status and DNAm age.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, additional factors beyond time have been shown to influence DNAm age, such as genetic diseases [ 3 , 4 ], infectious diseases [ 5 ], inflammatory disorders [ 6 , 7 ], and lifestyle factors, such as exercise and obesity [ 8 ], to cite a few. DNAm data was also significantly correlated to mortality risk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%